Autochthonous probiotic mixture improves biometrical parameters of larvae of Piaractus mesopotamicus (Caracidae, Characiforme, Teleostei) - Guidoli, Marcos Gabriel (2018)
Fil: Guidoli, Marcos Gabriel. Universidad Nacional del Nordeste. Facultad de Ciencias Veterinarias. Instituto de Ictiología del Nordeste; Argentina.